INFORMATION TECHNOLOGY IN AI-DRIVEN LEARNING INNOVATIONS, IMPACTS AND ETHICAL CHALLENGES - Wan Abdul Rahim Wan Mohd Isa; Nor Liyana Mohd Shuib (Penerbit UTHM, 2026)
The convergence of Artificial Intelligence and Information Technology is fundamentally reshaping the educational landscape. Information Technology in AI-Driven Learning: Innovations, Impacts and Ethical Challenges offers an essential guide to this digital transformation. Using a narrative review methodology, this research book provides a holistic synthesis of this new territory. It moves beyond fragmented discussions to connect IT innovations from adaptive platforms to intelligent tutoring systems with their real-world impacts on learners. Crucially, it confronts the critical ethical challenges that arise, from algorithmic bias and data privacy to the governance of AI in our institutions. Across its eight interconnected chapters, this volume integrates theory and empirical findings, providing educators, researchers, and policymakers with a clear roadmap for harnessing AI responsibly. This book advocates for a humancentered integration of technology guided by equity and the enduring goal of enriching human learning experiences.